Estimation of Ibuprofen in Bulk and Tablets Using Ibuprofen Sodium as Hydrotropic Solubilizing Agent - Maheshwari, R.K.; Bishnoi, S.R.; Kumar, D.; Murlikrishna, N.V. (Asian Journal of Chemistry, 2010)
In the present investigation, hydrotropic solubilization phenomenon has been employed to solubilize the poorly water-soluble antiinflammatory drug, ibuprofen by use of 0.5 M of ibuprofen sodium (an economic drug) solution to carry out titrimetric analysis (in bulk drug sample and tablets) precluding the use of organic solvents. The methods are new, simple, accurate, reproducible, inexpensive and eco-friendly. The results of analysis by proposed methods of analysis compared well with the results of standard pharmacopoeial methods. Recovery studies and statistical parameters validated the proposed methods.